What is the level of self-reported physical activity in people with multiple sclerosis in the Czech Republic? - Novotná, Klára; Šmejkalová, Barbora; Horáková, Dana; Větrovská, Renata (Journal of nursing, social studies and public health, 2024)
Background: Information about the level of physical activities in people with multiple sclerosis (MS) is available from a number of countries, but not from Central European countries. No data has been published from the Czech Republic so far. The aim of our study was to investigate the type and level of physical activities/exercise in people with MS in the Czech Republic, along with the clinical factors that may influence these physical activities. This information can assist nurses in advising on complex patient care. Methods: The clinical assessment included: the Godin–Shephard Leisure Time Physical Activity Questionnaire (GLTEQ), the 25-foot walk test (T25FW), the 2 Minute Walk Test (2MWT), the Fatigue Severity Scale (FSS), and a study-specific questionnaire that reports experience with sports and sport activities or rehabilitation exercises. Results: In our sample of 308 people with MS, 63% reported engaging in some form of physical activity. Men exercise more regularly, while irregular exercise predominates among women. Cycling and swimming are the most popular forms of physical activity for both genders. Only one third of participants exercise several times a week – as per medical recommendations. When comparing the mean values, men are classified as active and women as moderately active (according to the GLTEQ questionnaire scores). In our sample, no strong correlations were found between physical activity level and the clinical characteristics of the patients. Weak correlations were found only for fatigue (r = –0.32), neurological disability (r = –0.22), and walking ability (r = 0.25). Conclusion: Since regular physical activity is considered an integral part of the complex treatment of MS patients, this information can help nurses in counselling patients.